Model values of motor abilities of junior rhythmic gymnasts in the Republic of Croatia (Kinesiology, 2019)
Knowledge of the current status of motor abilities allows valid evaluation of the objective situation and forecast further development of rhythmic gymnasts. The main objective of this research was to determine the difference and connection between the motor abilities of rhythmic gymnasts depending on the program level, biological age and achieved national ranking.Research results stemming from using multivariate analysis of variance showed a statistically significant difference in the estimated motor abilities between junior rhythmic gymnasts in A, B and C level programs. The univariate analysis of variance has shown that differences in motor skills between rhythmic gymnasts’ different programs were statistically significant. A-level rhythmic gymnasts have produced better results in all tests for the assessment of flexibility, coordination and strength.The research related to differences in motor abilities between junior rhythmic gymnasts with regard to the achieved ranking showed no statistically significant difference, whereas biological age made a statistically significant difference. Pearson's correlation coefficient revealed significant relations between some motor abilities among rhythmic gymnasts in A, B and C level programs. The correlatives were higher as the level of the program was higher and vice versa.  Two tests had the largest contribution to the success achieved in the competition, the figure of eight with a bend test and bend on the bench test, which assesses overall flexibility.The scientific value of the proposed research is aimed at better planning, programming and control of the training process in rhythmic gymnastics.Keywords:  rhythmic gymnastics, program level,motor abilities